The relationship between coronary artery disease and pericoronary epicardial adipose tissue thickness - Aydin, Ayse Murat; Kayali, Alperen; Poyraz, Ahmet Kursad; Aydin, Kemal (Sage Publications Ltd, 2015)
Objectives A retrospective study to investigate the relationship between epicardial adipose tissue thickness (EATT) and presence of coronary artery plaque, coronary artery disease (CAD) and CAD risk factors. Methods Multidetector computed tomography (MDCT) coronary angiography images were reviewed. Left anterior decending artery, right coronary artery and left circumflex artery pericoronary EATT were measured. Demographic, clinical and CAD risk factor data were obtained from medical records. Results Patients with CAD (n=49) had significantly larger mean EATT than those without CAD (n=101). Pericoronary EATT was significantly correlated with body mass index, total cholesterol level, coronary artery calcium score, hypertension and diabetes mellitus history. Conclusions There is an association between pericoronary EATT and CAD, as well as CAD risk factors. Pericoronary EATT measurement may become a widely used, easy-to-perform method for determining CAD risk.
Keywords: Coronary artery disease; epicardial adipose tissue; multidetector computed tomography